Advancing human health risk assessment: the role of new approach methodologies - Deepika, Deepika; Bharti, Kanchan; Sharma, Shubh; Kumar, Saurav; Pathak, Rajesh Kumar; Biosca Brull, Judit; Sabuz, Oscar; García Vilana, Silvia; Kumar, Vikas (Frontiers in Toxicology, 2025)
New Approach Methodologies (NAMs) hold great potential to fill data gaps for chemicals and modernisation of chemical risk assessment practices. Current toxicity testing is based on conventional approaches with high reliability on in-vivo studies, but with time, regulators are trying to move towards in-vitro and in silico tools enabling efficient risk assessment strategies. Herein, we discuss about different emerging techniques which are or can become a NAM including both in-vitro and in silico models with particular focus on reducing animal studies and improving decision-making for hazard and exposure assessment. We also discussed about the way to strengthen the regulatory and public confidence in different NAMs and automation of these approaches. Some of these NAMs can help in identifying biochemical mechanisms for toxicity, calculate the point of departure (PoD), develop adverse outcome pathways (AOP), translate risk to multiple species and quantify uncertainty from predictions for multiple chemicals. Scientists and regulators can work together to frame robust guidelines for the practical application of these tools and ensure reproducible results.